2022
DOI: 10.1097/j.pain.0000000000002655
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic modulation of tumor necrosis factor alpha-induced nociception in the presence of oral squamous cell carcinoma

Abstract: Supplemental Digital Content is Available in the Text.Oral cancer mouse models were used to demonstrate that sympathetic neurotransmission modulates oral cancer pain and tumor growth through adrenergic signaling in the tumor microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
(166 reference statements)
1
8
0
Order By: Relevance
“…7 ); however expression of TH was found to be in very few TG neurons indicating that TH + nerves in the tongue are not sensory fibers ( Fig S3 A). This is in accordance to what we and others have observed in mice ( Atherton et al 2023 ; Wu et al 2018 ). Instead, our data confirmed that TH + nerve filaments were surrounding blood vessels indicative of sympathetic innervation ( Fig S3 B) .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…7 ); however expression of TH was found to be in very few TG neurons indicating that TH + nerves in the tongue are not sensory fibers ( Fig S3 A). This is in accordance to what we and others have observed in mice ( Atherton et al 2023 ; Wu et al 2018 ). Instead, our data confirmed that TH + nerve filaments were surrounding blood vessels indicative of sympathetic innervation ( Fig S3 B) .…”
Section: Discussionsupporting
confidence: 94%
“…We also tested for expression of TH expressing fibers in the tongue of marmosets as TH can be expressed in sensory neurons in mice ( Usoskin et al 2015 ) as well as is considered a marker for sympathetic innervation that has been shown to contribute to peripheral nociception ( Atherton et al 2023 ; Fan et al 2018 ). TH + fibers were indeed expressed in marmoset tongue and quantification of these fibers in the tongue showed no difference in the number of TH fibers (( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse transcription was performed with Quantitect Reverse Transcription Kit (Qiagen Inc.) according to the manufacturer's instructions. For single cell analysis, DiI-positive single neurons were dissociated as previously described ( 19 , 21 , 22 ), identified using fluorescence microscopy, and limited to ≤ 25 μm in diameter. Cells were then picked up using glass capillaries (World Precision Instruments) which were held by micromanipulator (Sutter Instruments), headstage (EPC10 HEKA) and electrode holder under brightfield optics.…”
Section: Methodsmentioning
confidence: 99%
“…However, Atherton et al identified postganglionic sympathetic nerves in C57Bl/6 mouse tongue tumors using a retrograde tracer that labeled neurons in the superior cervical ganglion. [51] Importantly, increased TH-positive nerve density is associated with aggressive OSCC. [49] Adv.…”
Section: Neural Influence In Oral Cavity Cancermentioning
confidence: 99%